Social Capital Strengthening Strategy for Maintaining Investment Sustainability in Lumajang Regency - ., Zainuri; Viphindrartin, Sebastiana; Asna, Silvi (International Journal of Engineering and Technology, 2018)
Lumajang Regency has various potentials to be developed. The geographical condition of the region as one of the potentials should be able to increase the regional income through investments. On the other hand, it has been identified that investment level and regional income have decreased. Based on field research, it is caused by global economic changes (interest, electricity, tax, etc.) and crimes. However, other conditions also exist. For example, there are some investors with no business declining using social capital strength. This study aims to uncover the strategy of social capital strengthening for maintaining investment sustainability in Lumajang Regency. This research employs qualitative phenomenology method. The results of this research indicate that there are two strategies used by investors for maintaining their business in the uncertain condition in Lumajang. First, Personal-Branding Strategy (PBS) is a strategy using personal approach by persuasive ways to create bounding social capital. Meanwhile, Self-Esteem Approach Strategy (SEAS) is a strategy using job competency and power to create linking social capital. This strategy can be used by the existing investors to re-start or maintain their business in Lumajang; it can also become one of considerations of potential investors on what they must do to reach sustainable and profitable business in Lumajang Regency. Â Â